1982
DOI: 10.1038/jcbfm.1982.32
|View full text |Cite
|
Sign up to set email alerts
|

Use of 2-Deoxy-D[1-11C]Glucose for the Determination of Local Cerebral Glucose Metabolism in Humans: Variation within and between Subjects

Abstract: tracer for the measurement of LCMRgl and to determine its variability within subjects over a 2-h period. The kinetic rate constants for ll C-deoxyglucose were determined for gray and white matter and found to be very similar to those for 18F-fluorodeoxyglucose, suggesting that these two analogues of glu cose have similar affinities for the facilitated transport system and are similar substrates for hexokinase in the brain. The coefficient of variation of repeated measurements of LCMRgl in a series of six norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…During the procedure, blood samples were obtained from an arterialized vein using a hand-warmer device to monitor for radioactive plasma concentration. The scanning and image recon struction were done using standard procedures (Reivich et a!., 1982). Each subject was scanned twice, once under baseline conditions (eyes open, ears plugged) and 3 h later while engaged in an eye-tracking visual task.…”
Section: Methodsmentioning
confidence: 99%
“…During the procedure, blood samples were obtained from an arterialized vein using a hand-warmer device to monitor for radioactive plasma concentration. The scanning and image recon struction were done using standard procedures (Reivich et a!., 1982). Each subject was scanned twice, once under baseline conditions (eyes open, ears plugged) and 3 h later while engaged in an eye-tracking visual task.…”
Section: Methodsmentioning
confidence: 99%
“…This latter range of intraindividual variability is considerably less than the 23.8% in traindividual variability obtained in our subjects for resting state studies. However, Reivich et al (1982) performed their second studies only 2 h after the first study, using [ ll C]deoxyglucose as the tracer, whereas we repeated studies after an interval of 1-6 weeks. In all likelihood, the difference in time interval between the first and second studies ac counts for the difference found in reliability of CMR g lu values in the two protocols.…”
Section: Discussionmentioning
confidence: 99%
“…was deemed unlikely. We therefore chose, as did Reivich et al (1982), to ignore this small and relatively constant (Hawkins et aI., 1981) component in our calcu lation. Thus, using raw arterial 18F data and elementary brain activity curves, each of the three FDG rate con stants (kj, ki, and kn was measured in elementary tissue volumes; this allowed a map of kinetic CMRGIc to be constructed using the equation CMRGlc = Ie / Lq .…”
Section: Methodsmentioning
confidence: 99%
“…First, the twelfth scan of the mid cut and the 18F images of the two adjacent cuts were transformed, pixel by pixel, into au toradiographic CMRGIc images using the 18F arterial data curve (obtained by either the heated-hand vein procedure or a radial artery catheter) and the four-constants oper ational equation devised by Phelps et al (1979) with the standard FDG rate constants (k*) and lumped constant (LC = 0.42) values reported by these authors. Second, following the principle set forth by Sokoloff et al (1977) and applied in human PET studies by Huang et al (1980) and Reivich et al (1982), the 12-scan series of the midcut was processed to obtain local estimates of the real 18FDG rate constants. To do this, the original 18F images were first changed from a 100 x 100 matrix into a 25 x 25 matrix to improve the statistical validity of the approach.…”
Section: Methodsmentioning
confidence: 99%